Are visceral adiposity index and ultrasonographic visceral fat thickness measurements correlated to endometrial thickness in postmenopausal women? - Fatma Eskicioglu; Muhammet Sakıp Eskicioglu; Beyhan Ozyurt (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2019)
Objective: During the postmenopausal period, visceral fat tissue is responsible not only for increased cardiometabolic risk, but also for endocrine function leading to increased endometrial thickness (ET). The current study aimed to 1) determine the predictive value of ultrasonographic visceral fat thickness (VFT) and the visceral adiposity index (VAI), which is defined as «an indicator of visceral adipose function,» for the prediction of an ET>5 mm and 2) to search for a correlation between these two measures. Materials and Methods: In 79 postmenopausal women, VFT and VAI measurements were compared between a group of patients with an ET>5 mm and a group with an ET ≤ 5 mm. The diagnostic performances of VFT and VAI were investigated. Results: There were no significant differences between the two groups with respect to the VFT and VAI values. Positive correlations were observed between the VFT and VAI, as well as between VFT and ET (r=0.242, p=0.03 and r=0.217, p=0.05).  Conclusion: VFT and VAI values are correlated in postmenopausal women. However, neither VFT nor VAI appears to have a predictive value for an ET>5mm. Additional studies need to be performed on this subject.